Pengaruh Model Pembelajaran Cooperative Integrated Reading Composition Terhadap Kemampuan Pemahaman Bacaan Siswa Sekolah Dasar Pada Mata Pelajaran Bahasa Indonesia - Lena Amelia; Mas Roro Diah Wahyu Lestari (Universitas Muhammadiyah Kuningan, 2024)
This research was motivated by students' low reading comprehension abilities and the lack of student activity in classroom learning activities. The aim of this research is to determine the effect of the cooperative integrated reading composition learning model on fourth grade students' reading comprehension ability with story material. The method used in this research was quasi-experimental, with a sample size of 30 experimental class students and a one-group pretest-posttest design. The results of this research can be seen from the results of calculations using the Paired Sample t-Test type t test and the t test results obtained with a t value of 25.202, which can be interpreted as greater than t table 2.042, with a significance level of 0.000 < 0.05, so that H0 is rejected and Ha is accepted. These results can be interpreted as meaning that there is an influence of the cooperative integrated reading composition learning model on students' reading comprehension abilities in class IV of MIS Al-Hidayah. It is hoped that the results of this research will be useful for school principals, teachers, students, and future researchers.